Controlled synthesis of conjugated polycarbazole polymers via structure tuning for gas storage and separation applications. Issue 1 (December 2017) - Li, Guoyan; Qin, Long; Yao, Chan; Xu, Yanhong
Abstract A series of conjugated microporous polymers (CMPs) based on 1, 3, 6, 8-tetrabromocarbazole (N4 CMP-1–5) is synthesized via Suzuki cross-coupling or Sonogashira polycondensation. The porosity properties and surface area of these polymer networks can be finely tuned by using a linker with different geometries or strut length. These polymers show the Brunauer-Emmett-Tellerthe (BET) surface areas ranging from 592 to 1426 m2 g−1 . The dominant pore sizes of the polymers on the basis of the different linker are located between 0.36 and 0.61 nm. Gas uptake increases with BET surface area and micropore volume, N4 CMP-3 polymer can capture CO2 with a capacity of 3.62 mmol g−1 (1.05 bar and 273 K) among the obtained polymers. All of the polymers show high isosteric heats of CO2 adsorption (25.5–35.1 kJ mol−1 ), and from single component adsorption isotherms, IAST-derived ideal CO2 /N2 (28.7–53.8), CO2 /CH4 (4.6–5.2) and CH4 /N2 (5.7–10.5) selectivity. Furthermore, N4 CMPs exhibit the high CO2 adsorption capacity of 542–800 mg g−1 at 318 K and 50 bar pressure. These data indicate that these materials are a promising potential for clean energy application and environmental field.